Los costos y su influencia en la fijación de precios de las comidas y bebidas del restaurante de la hostería Ugsha Wasi del cantón pujilí en el año 2013 - Tocumbe Tigasi, María Alicia (2015)
This research work had as general objective to propose a cost system that allows the pricing in the preparation of meals and drinks, to ensure greater profitability in the restaurant of the hostel. The instruments and methods used for analysis and data collection were surveys and interviews which helped identify clearly the situation of the company. It was determined that the main problem of the inn is that you do not have a cost system that allows adequate control of cost elements that are the raw material, labor and manufacturing overhead costs, as they only they do so entirely at their experiences or based on the market….